Screening for Developmental Disorders in 3- and 4-Year-Old Italian Children: A Preliminary Study - Catino, Elena; Di Trani, Michela; Giovannone, Federica; Manti, Filippo; Nunziata, Letizia; Piccari, Francesca; Sirchia, Virginia; Vannucci, Lucia; Sogos, Carla (Frontiers in Pediatrics, 2017)
Background: The “Osserviamo” project, coordinated by the Municipality of Rome and the Department of Pediatrics and Child Neuropsychiatry of Sapienza University, aimed to validate an Italian version of the Ages and Stages Questionnaire-3 and to collect, for the first time in Italy, data on developmental disorders in a sample of 4,000 children aged 3 and 4 years. The present paper presents the preliminary results of the “Osserviamo” project. Methods: 600 parents of children between 39 and 50 months of age (divided in two age stages: 42 and 48 months) were contacted from 15 kindergarden schools. Results: 23.35% of the whole sample scored in the risk range of at least one developmental area of the ASQ-3 and 7.78% scored in the clinical range. Specifically, 23.97% of the children in the 42-month age stage scored in the risk range and 5.79% scored in the clinical range. Males scored lower than females in the Fine motor skills and Personal-social development domains. Moreover, 22.79% of the children in the 48-month age stage scored in the risk range while 9.55% scored in the clinical range. Males scored lower than females in Fine motor skills. Conclusions: Italian validation of the ASQ-3 and recruitment of all 4,000 participants will allow these data on the distribution of developmental disorders to be extended to the general Italian pediatric population. One main limitation of the study is the lack of clinical confirmation of the data yelded by the screening programme, which the authors aim to obtain in later stages of the study.